MELACAK JEJAK IBN MASKAWAIH DALAM POLITIK DINASTI BUWAIHI - Zaki Mubarok (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2015)
Ibn Miskawayh is one which has a concentration of Muslim intellectuals in the moral sphere but largely forgotten. This is because in some basic literature not found in most biographies and thoughts completely. Basic information can be found in the dissertation Suwito which was later published under the title Moral Education Philosophy Ibn Miskawah. In the book there is a short information that Miskawayh is a figure who lived during the dynasty Buwaih. Incompleteness of this biography can also referenced in the book Ismail Raji al Faruqi and Lois Lamya al-Faruqi, entitled Atlas of Islamic culture, in assessing the spread of Islam from the Arab region, Persian, Byantium, Egypt, North Africa did not mention anything about Ibn Miskawayh and Bani Buwaih included in the study. Things like this are also found in the book Lothop Stodart, New World of Islam. In the introduction to study about Islam that began the process of deterioration of displacement Caliphate from Medina to Damascus, Syria, and to Baghdad. In Baghdad this in the review period several dynasties and important figures who played but once again Ibn Miskawayh and Buwaihi unnoticed.Keywords: Ibn Miskawaih, moral education, politics, Bani Buwaihi